Impactos da estratégia de diversificação na estratégia de produção: estudo de caso da empresa Vilma Alimentos - Amara Fuccio de Fraga e Silva (2004)
Technological advances occurring in recent decades have created impacts on society and economy as a whole. On the other hand, comecial oppening and deregulation of the wheat industry in Brazil at the beginning of the 90s, demanded change of organizations involved in this sector to face new competitors who entered this market. Companies are forced to become more agile to go ahead or monitor the demand´s movement and competition. In that sense, there is a quest for greater versatility and agility as the actions of the organization, demanding at the same time a relaxation and an integration with the entire party. Thus, there are incorporations of advanced technologies for processing of philosophies to work more participatory and reconfiguration of its operating systems to become more flexible. For both, there is a restructuring in order to build the strategies as functional as well as the actual relationship interfuncional. Thus, this study was compiled from the study of the company Vilma Foods, identifying, from the 90s, which were its strategic moves in corporate strategy and how to get involved in production and how it has been supported the new positioning of the company . In other words, what were the mechanisms of settings, how the strategies are built and how the manufacturing is set to meet new market demands and more diverse to maintain their competitiveness. The results of this research show that the formulation of corporate strategy has become much more dynamic and participatory, built over the organization's daily, inserted into a more procedural. Furthermore, the specificity of the production of pasta products requires final with a variety of formats and made from various types of wheat. In this sense, there was an increase technology, with the acquisition of flexible lines not working, giving support to the company's guidance of increased mix of products and the easing of lots and delivery time, all with the goal of acting in various niche markets. As the main contribution that is sought in this research has been discussing the formulation of strategies, and not dedicated to flexible manufacturing allows the configuration of production systems in search of greater flexibility.